Choroidal thickness in relation to diopter and axial length among myopic children - Zhu, Huailin; Liu, Changyang; Gao, Mingjun; Zhang, Siqi; Zhang, Lan; Zhao, Qi (Frontiers in Medicine, 2023)
The aim of this study was to analyze the relationship between diopter (D) and choroidal thickness in myopic children by describing the values of choroidal thickness, and explore choroidal thickness as an important indicator for evaluating the progression of myopia.The study included myopic and emmetropic children aged 6-14 years (156 eyes) from the Second Hospital of Dalian Medical University. The participants were divided into four groups according to the spherical equivalent refraction (SER): low myopes, moderate myopes, high myopes, and emmetropes. Choroidal thickness was measured in nine areas using the Early Treatment Diabetic Retinopathy Study (ETDRS) grid layout, which divided the areas into concentric circles of 0×0 mm, 3×3 mm, and 5×5 mm from the subfovea. The images were obtained manually with spectral-domain optical coherence tomography scanner.Results: There were significant differences of choroidal thickness in the nine areas of the ETDRS grid for all myopes. The distribution of choroidal thickness in low and moderate myopes were different from that in high myopes. In the horizontal direction, choroidal thickness decreased from the temporal to nasal areas for all myopes. In the vertical direction, the choroidal thickness in the perifovea was smaller than that in the parafovea (SER ≥ -2.75D), and the choroidal thickness in the perifovea was greater than that in the parafovea (SER < -2.75D). When comparing emmetropes with myopes, the closer the choroidal thickness was to the central fovea, the more significant the differences were, while the differences were smaller to the perifovea. Among all children, choroidal thickness was positive to SER and negative to axial length (AL) in all areas. For every 1D increase in myopia, the subfoveal choroidal thickness decreased by 13 μm, and for every 1 mm increase in AL, the subfoveal choroidal thickness decreased by 23 μm. Furthermore, SER and AL showed the strongest correlation with choroidal thickness in the inferior area.Optical coherence tomography results revealed choroidal thickness was thinner in myopic children. Choroidal thickness was positive to SER and negative to AL. Therefore, we consider choroidal thickness to be an important indicator for evaluating the myopia progress.